The Concept and Implementation of Knowledge Management in the SME Sector - Suasih, Ni Nyoman Reni; Wijaya, Putu Yudy (Technium Social Sciences Journal, 2021)
Managing knowledge and human resources is an important element in running all types of businesses. Knowledge management is considered the best strategy used by business people to win the competition because knowledge is a strategic source that enables them to obtain a higher level of competitiveness and innovation. Therefore, the potential for knowledge management and intellectual capital as a source of innovation and renewal, business strategies must focus more on these issues. Knowledge management involves knowledge acquisition, knowledge sharing, and application of knowledge. The overall aim of knowledge management is to utilize information and competency knowledge that is the main source of the company's main source of competitive advantage. Knowledge management emerges as an important concept and is often cited as an antecedent of innovation, competitiveness, and also business performance of SMEs.